2014
DOI: 10.1109/tap.2014.2330572
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Calculation of Mutual Coupling Between Apertures on a Large Coated Cylinder Using Mixed Potential Green's Functions

Abstract: A rigorous approach based on the closed-form mixed potential Green's function (MPGF) is developed to evaluate mutual coupling between apertures on an electrically large cylinder with dielectric covers. An improved procedure is outlined to provide accurate values of the MPGF both in the near and far field, including the axial line region. The cylindrical functions are represented in the form of ratios to avoid the numerical instabilities, making the MPGF able to handle electrically large problems. As a result, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The cylindrically stratified medium that models the multilayered cylindrical dielectric radome together with free-space as the outermost layer forms Region II, for which new closed-form GF (CFGF) representations are developed for tangential magnetic currents. Note that although several studies on CFGF representations for cylindrically stratified media have already been reported to be used in conjunction with MoM for the design and analysis of microstrip and slot/aperture antennas and arrays [9]- [18], they are not valid within the source region (where two current modes can partially or fully overlap during the MoM procedure). Recently, reported CFGF representations for tangential electric current modes in [19] are valid and very accurate within the source region.…”
Section: Introductionmentioning
confidence: 99%
“…The cylindrically stratified medium that models the multilayered cylindrical dielectric radome together with free-space as the outermost layer forms Region II, for which new closed-form GF (CFGF) representations are developed for tangential magnetic currents. Note that although several studies on CFGF representations for cylindrically stratified media have already been reported to be used in conjunction with MoM for the design and analysis of microstrip and slot/aperture antennas and arrays [9]- [18], they are not valid within the source region (where two current modes can partially or fully overlap during the MoM procedure). Recently, reported CFGF representations for tangential electric current modes in [19] are valid and very accurate within the source region.…”
Section: Introductionmentioning
confidence: 99%